Penerapan Dashboard Excel Otomatis untuk Meningkatkan Tata Kelola dan Konsistensi Pencatatan Keuangan UMKM - Deana Putri Angelene; Hartati Hartati; Daniel Sugama Stephanus; Tarsisius Renald Suganda; Rino Tam Cahyadi; Bagas Brian Pratama (CV. ITTC INDONESIA, 2025)
Yan’s Keramik is a micro, small, and medium enterprise (MSME) engaged in ceramic handicrafts since the early 2000s. In its operations, Yan’s Keramik still faces challenges in implementing a structured financial recording system that aligns with fundamental accounting principles. Therefore, this community service activity aims to assist Yan’s Keramik in improving the quality of its financial recording and reporting, enabling it to accurately reflect the business’s actual financial condition. Through this initiative, it is expected that the MSME will be able to prepare simple yet well-organized financial statements that support more precise, data-driven decision-making. The implementation method used is qualitative, employing interviews and direct observation of the MSME’s financial activities. During the mentoring process, the service team collected data directly from the business owner and identified financial recording needs tailored to the characteristics of the enterprise. To enhance the effectiveness of the program, a participatory approach was also applied by involving the business owner in each stage of the process, ensuring that the resulting solutions genuinely reflect real needs in the field. The outcome of this activity was the development of a financial recording template using Microsoft Excel, equipped with formulas and automated reporting formats. This template is expected to help Yan’s Keramik manage its finances in a more organized manner and prepare income statements and cash flow reports on both a monthly and annual basis. One of the main challenges identified was the lack of separation between personal and business finances, which has made it difficult to objectively assess the performance of the business.